Journalist Credibility Based On Digital Media Used - Suraya Suraya (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2019)
This research studies the digital media consumption pattern of journalists. This consumption pattern is done by journalists to support their job. The work pattern of journalists in finding news fundamentally depends on the credibility of the sources. The process of choosing sources and finding ideas and information is usually done conventionally, thus presently done through social media. This study was conducted by surveying 60 journalists in Jakarta. The method used for data analysis was descriptive statistics. Results showed that the majority of respondents had a high social media usage pattern; thus, it can be said that social media carries a great influence toward the work pattern of journalists. This can be seen from the majority of respondents who admitted that they had written about growing issues in social media as news in conventional media; they even admitted to interviewing some sources because they monitored their opinions and comments on social media. The type of journalists who became respondents in Jabodetabek were creators, conversationalists and Joiners; the rest participated by consuming social medias and collecting informations. Journalists in this position acted only as consumers.